2022
DOI: 10.1111/pce.14459
|View full text |Cite
|
Sign up to set email alerts
|

The active Fe chelator proline‐2′‐deoxymugineic acid enhances peanut yield by improving soil Fe availability and plant Fe status

Abstract: Iron (Fe) deficiency restricts crop yields in calcareous soil. Thus, a novel Fe chelator, proline-2′-deoxymugineic acid (PDMA), based on the natural phytosiderophore 2′-deoxymugineic acid (DMA), was developed to solve the Fe deficiency problem.However, the effects and mechanisms of PDMA relevant to the Fe nutrition and yield of dicots grown under field conditions require further exploration. In this study, pot and field experiments with calcareous soil were conducted to investigate the effects of PDMA on the F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…1). 15 In addition, PDMA was also shown to be effective for cucumbers and peanuts in calcareous soil, [16][17] suggesting that PDMA is applicable to all plant species, not just the Poaceae. Most recently, the structure of HvYS1, the YS1/YSL transporter of barley, was elucidated by cryo-electron microscopy, and structural analysis revealed that the PDMA-Fe(III) complex passes the same binding site as DMA-Fe(III), meaning that PDMA functions as a fertilizer in exactly the same manner as natural DMA.…”
Section: Introductionmentioning
confidence: 99%
“…1). 15 In addition, PDMA was also shown to be effective for cucumbers and peanuts in calcareous soil, [16][17] suggesting that PDMA is applicable to all plant species, not just the Poaceae. Most recently, the structure of HvYS1, the YS1/YSL transporter of barley, was elucidated by cryo-electron microscopy, and structural analysis revealed that the PDMA-Fe(III) complex passes the same binding site as DMA-Fe(III), meaning that PDMA functions as a fertilizer in exactly the same manner as natural DMA.…”
Section: Introductionmentioning
confidence: 99%
“…It is unclear whether WS affects hormones related to the regulation of starch and sucrose metabolism and kernel weight in peanuts. Transcriptomic and metabolomic analyses have been widely used to investigate the dynamic expression of genes related to starch and sucrose metabolism (Shen et al, 2022; Wang et al, 2023; Yang et al, 2022; Zhang et al, 2015), fatty acid metabolism (Xu et al, 2022), amino acid synthesis (Lou et al, 2022), and flavour formation (Wang et al, 2021) during kernel filling. Therefore, the waterlogging‐sensitive peanut variety, Huayu 39, was selected to examine the key developmental stages during which WS affects kernel filling.…”
Section: Introductionmentioning
confidence: 99%